Use of the clinical debriefing technique in medical simulation for decision making in medical students at a private university in Northern Mexico. - A.G., Saucedo Aparicio; N.D., Betancourt Martínez; F.F., González Galarza; P., Ruíz Flores; C.O., Puente Valenzuela; S.E., Espinosa Padilla; J., Moran Martínez (Revista de Ciencias Médicas Torreón, 2025)
Arsenic (As) is a metalloid widely recognized for its toxicity, particularly when present in drinking water, where it poses a significant public health threat. In regions such as the Comarca Lagunera, Mexico, arsenic contamination has reached alarming levels due to geological, climatic, and anthropogenic factors. This article reviews the chemical properties of arsenic, its environmental mobility, sources of exposure, and toxicity mechanisms. The negative effects of arsenic on human health are highlighted. Additionally, the challenges faced by vulnerable groups, who are at greater risk due to higher exposure and susceptibility, are addressed. Finally, perspectives on mitigation strategies are presented, along with the need for further research on long-term effects and innovative technological solutions.